Eikón Imago (Universidad Complutense, 2012)
Eikón Imago is a scientific journal published by the Research Group CAPIRE (Collective for the Pluridisciplinary Analysis of European Religious Iconography), attached to the Department of History of the Art of the School of Geography and History at the Complutense University of Madrid.The research interest of this journal focuses on iconography in a broad sense, with a thematic coverage that aims the forms and meanings of the images of any era, culture or country, as well as any thematic, typological or disciplinary variant of the iconograph: religious, mythological, political, musical, fantastic, animalistic or other